DAMPAK PEMBERIAN PUNISHMENT TERHADAP DISIPLIN KERJA KARYAWAN - Dedi Hartawan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
This study was motivated by the importance of the punishment system in improving employee discipline LAZNAZ DPU (Dompet Peduli Ummat) Daarut Tauhiid. The population in this study were all employees of LAZNAZ DPU (Dompet Peduli Ummat) Daarut Tauhiid totaling 109 people. The sample in this study is the number of employees of PT. Citra Riau Sarana numbering 8. The data used in this study are primary data and secondary data. Analysis of the data used is using simple linear regression analysis with significance level of 5%. Data processing is done with the help of SPSS software version 16.0. From the results of simple linear regression analysis Punishment (X) influence to to the discipline of employees (Y).